Kompetensi Pedagogik Guru Bahasa Indonesia Di MTs Negeri 2 Medan Dan MTs Laboratorium UINSU - Nisa Hafzhiyah Hasibuan; Ummi Nur Afinni Dwi Jayanti; Meutiah Khairani Harahap; Syafina Maulani; Tantri Adelia; Dwi Setia Ningsih; Elfina Wetty (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
Pedagogical competence is the ability to manage student learning, including understanding, designing and implementing, evaluating learning outcomes and developing various student potentials. This study aims to describe the pedagogic competence of Indonesian teachers at MTs Negeri 2 Medan and MTs Laboratory of the University of Indonesia. This type of research is qualitative research using descriptive methods. This research was conducted in several Madrasah Tsanawiyah in Medan City. The data sources in this study were school principals and Indonesian language teachers. Data collection techniques were carried out by observation, interviews and open questionnaires. The research instrument consisted of researchers and supporting instruments in the form of observation guidelines, interviews and data analysis guidelines. The results of the study revealed that school principals and teachers have an in-depth understanding of educational insights and foundations, teachers are able to understand the characteristics of students by taking various approaches, principals provide assessments of teacher pedagogical competence in schools they lead, teachers are able to understand students and the difficulties they face in learning, the teacher is able to design and carry out educational learning by carrying out various methods and strategies in learning, the teacher utilizes the technology provided in learning, the teacher evaluates students in several ways to see the abilities of students, the teacher develops students to actualize their potential by providing support and direction to students to develop their interests and talents.